Pelatihan Pembuatan Digital Brosur Promosi UMKM di Kabupaten Banyumas - Gigih Ariastuti Purwandari; Indah Puspitasari; Kristianto Setiawan; Eka Dyah Puspita Sari; Lely Tri Wijayanti (LPPM UNIVERSITAS DIAN NUSWANTORO, 2024)
AbstractThe community service is aimed to provide knowledge about brochure visualization. The method used to achieve these objectives involves activities such as presentations, training, and mentoring, which include knowledge building, modeling, joint construction, and independent construction activities. To measure the success of the activity, there are three types of evaluation: (1) the initial stage through a Pre-test. Questions are posed through a Google form to assess the participants' initial knowledge, (2) the implementation stage/process of the activity through observation, discussion, practice, and assessment of the final products, and (3) the final stage through a post-test, where answers are assessed to determine the knowledge improvement after participating in this PkM. With these evaluation stages, the knowledge and skills of the participants are assessed to understand their improved understanding of brochure visualization knowledge and skills. As a result, there is an increase in knowledge about brochure visualization. Through this activity, issues related to optimizing knowledge and skills in brochure visualization can be addressed.